Prognostic factors of nervous system damage in children with COVID-19 - Seriakova , Iryna; Kolte, Roohi; Kramarov , Sergiy (The Ukrainian Scientific Medical Youth Journal, 2023)
this work is devoted to the study of the features of the structure of symptoms related to the nervous system in children with coronavirus disease (COVID-19). During the COVID-19 pandemic, there is a rapid increase frequency of neurological lesions. The share of neurological manifestations in COVID-19 among adult patients is up to 82%, in children it ranges from 3% to 47%. The aim of the work was to study the frequency and structure of neurological symptoms in children who were hospitalized in an infectious disease hospital with a laboratory-confirmed diagnosis of COVID-19 during 2020-2022 and to determine prognostic factors of nervous system damage. Materials and methods: We retrospectively investigated 945 medical histories of children aged from birth to 18 years who were hospitalized at the Kyiv City Children's Infectious Disease Hospital ("KCCIDH") in Kyiv, Ukraine during the pandemic. Among them, we analyzed cases accompanied by neurological symptoms. Features of the clinical picture, laboratory and demographic-epidemiological data were determined. The statistical calculation of the obtained results was carried out by using the statistical package Statistical software EZR v. 1.54. Results: Neurological symptoms were detected in 142 (15%) children, the majority of them were adolescents (55.6%). The leading symptoms of nervous system involvement were headache, ageusia/anosmia, convulsive syndrome, acute polyneuropathy, and myalgia/arthralgia. According to the analysis of odds ratio developing of neurological symptoms among patients in our cohort, children of the older age group (10-18 years) had statistically greater chances developing of neurological manifestations. Odds ratio developing of the aforementioned symptoms depending on clinical syndromes were also analyzed. Among respiratory syndromes, the presence of cough (5.53; 95%CI 3.53-8.65) and signs of lower respiratory tract inflammation (1.8; 95%CI 1.21-2.67) were associated with a higher risk of nervous system symptoms damage. According to the study of laboratory indicators, an increased level of leukocytes (2.01; 95%CI 1.2-3.38) was associated with an increase frequency of neurological manifestations, and in groups of patients with an increased level of C-reactive protein (0.39; 95%CI 0.23-0.68) or procalcitonin (0.21; 95% CI 0.11-0.43), on the contrary, a lower frequency of neurological symptoms was observed. Conclusions: Neurological symptoms occur in 15% of children with COVID-19. According to the results of our work, the older age of the child, cough and symptoms of inflammation of the lower respiratory tract are the prognostic factors of the occurrence of neurological symptoms in children with COVID-19. In addition, our study demonstrated the prognostic value of the appearance of neurological symptoms with an increase in the leukocyte index, as well as the absence of a correlation of neurological symptoms with an increase in CRP and procalcitonin.